The hippocampus contributes to temporal duration memory in the context of event sequences: A cross-species perspective. (3rd February 2020) - Lee, Andy C.H.; Thavabalasingam, Sathesan; Alushaj, Denada; Çavdaroğlu, Bilgehan; Ito, Rutsuko
Abstract: Although a large body of research has implicated the hippocampus in the processing of memory for temporal duration, there is an exigent degree of inconsistency across studies that obfuscates the precise contributions of this structure. To shed light on this issue, the present review article surveys both historical and recent cross-species evidence emanating from a wide variety of experimental paradigms, identifying areas of convergence and divergence. We suggest that while factors such as time-scale (e.g. the length of durations involved) and the nature of memory processing (e.g. prospective vs. retrospective memory) are very helpful in the interpretation of existing data, an additional important consideration is the context in which the duration information is experienced and processed, with the hippocampus being preferentially involved in memory for durations that are embedded within a sequence of events. We consider the mechanisms that may underpin temporal duration memory and how the same mechanisms may contribute to memory for other aspects of event sequences such as temporal order. Highlights: Cross-species evidence supports a role for the hippocampus in duration memory. Discrepancies in findings cloud the conditions governing hippocampal involvement. We suggest the importance of considering the hippocampus as a sequence processor. The hippocampus supports duration memory in the context of event sequences. Overlapping hippocampal mechanisms may support memory for duration and order.